2010
DOI: 10.1002/pssa.200983314
|View full text |Cite
|
Sign up to set email alerts
|

In situ cross‐linking of the shell of self‐assembled peptide nanotubes

Abstract: Peptide polymer nanotubes (PPNTs) were prepared by in situ surface-initiated atom transfer radical polymerization (ATRP) from self-assembled cyclic peptide nanotubes. PPNT dimensions, i.e., height (i.e. diameter) and length, as derived from AFM measurements of surface-adsorbed, dry PPNT are a function of the molar mass of the peptide-attached polymer molecules, and the overall structure is determined by subtle interplay of peptide-peptide and polymer-polymer interactions. As shown in previous communications, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Polymers have been conjugated to D,L-α-CPs in order to change the nanotube properties. [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] These macromolecules not only offer the possibility of introducing a wide variety of functionalities on the outer surface of the nanotube but also provide some control over the length by preventing the unlimited stacking of peptides. Different strategies have been developed for the preparation of hybrids of CPs and polymers and these approaches can be performed either before or after SCPN formation.…”
Section: Macromolecule Covalent Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers have been conjugated to D,L-α-CPs in order to change the nanotube properties. [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] These macromolecules not only offer the possibility of introducing a wide variety of functionalities on the outer surface of the nanotube but also provide some control over the length by preventing the unlimited stacking of peptides. Different strategies have been developed for the preparation of hybrids of CPs and polymers and these approaches can be performed either before or after SCPN formation.…”
Section: Macromolecule Covalent Functionalizationmentioning
confidence: 99%
“…More recently, another grafting from approach was used to prepare crosslinked polymeric nanotubes by growing ethylene glycol dimethacrylate from SCPNs. 82 The combination of solvents plays an important role in the assembling properties of the CP. For example, the use in the polymerization process of DMSO instead of mixtures of acetonitrile/toluene or isopropanol/toluene led to the divergent growth of polymers from the peptide prior to self-assembly of the aggregate (Fig.…”
Section: Macromolecule Covalent Functionalizationmentioning
confidence: 99%
“…A nice example of cross-linking these type of tubes has been shown by Biesalski and coworkers, who polymerized ethylene glycol dimethacrylate (EGDMA) divergently from the surface of a preassembled tube. 42 In addition to providing stable nanotubes such as these, our approach makes it possible to tune the length of the tubes prior to locking in the structure with the cross-linking reaction.…”
Section: Internal Structure Of the Nanotubes By Selective Deuterationmentioning
confidence: 99%
“…One apparent method to precisely direct nanotube assembly is to introduce one or more covalent linkages between CP monomers. Tethered CP homodimers have previously been produced by disulfide bond formation, metathesis of homoallylglycine containing CP monomers, by amide formation between Glu and Lys side chains, through photo‐switchable azobenzene linkers, and by cross‐linking with polymers . More recently, Fuertes et al.…”
Section: Figurementioning
confidence: 99%
“…There are only alimited number of examples of heterogeneous peptide nanotube systems [4c,6] and there has been little investigation of methods for directing the assembly process.O ne apparent method to precisely direct nanotube assembly is to introduce one or more covalent linkages between CP monomers.T ethered CP homodimers have previously been produced by disulfide bond formation, [8] metathesis of homoallylglycine containing CP monomers, [8,9] by amide formation between Glu and Lys side chains, [10] through photo-switchable azobenzene linkers, [11] and by cross-linking with polymers. [12] More recently, Fuertes et al reported heterogeneous nanotubes assembled from CP dimers that were made using ac opper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction to couple reactive handles attached to peptide backbone nitrogen atoms. [13] Herein, we describe the construction of tetrameric, heterogeneous cyclic d / l peptide subunits that provide improved control over CP nanotube composition and advance our program to develop peptide nanorods of controlled structure and length.…”
mentioning
confidence: 99%